Can the Audit Opinion Influence the Portfolio Investment Decisions? The Case of Listed companies - George-Marian AEVOAE (Chamber of Financial Auditors of Romania, 2021)
As a part of their strategic transactions, corporations often acquire stakes in other companies that do not grant them control, but allow them to use their resources to increase their profitability, access technological progress and innovation, develop products, or obtain dividends. The main objective of this paper is to identify the factors influencing the behavior of acquirers who buy securities in the capital of the target companies, listed on Bucharest Stock Exchange, without intending to control them. The study aims to describe two dimensions of the buyers' behavior, when they buy shares that do not lead to the control of the target companies (below 50%). The first dimension refers to the buyer's decision to invest in a certain share of capital, influenced by the profitability of the target company and its market capitalization (dimensions of their performance), but also by the audit opinion on the annual financial statements. The relationship is positive and significant. The second dimension focuses on the decision of the acquirers to invest or not in a blue-chip company (top companies, considered the most efficient and stable on the financial market), with the main purpose of obtaining dividends or trading the respective securities on the capital market, in order to generate cash flows. The result shows that investors buy small shares in blue chip companies, compared to other companies, taking into account their performance and the audit opinion on the annual financial statements.